2021
DOI: 10.3390/plants10112391
|View full text |Cite
|
Sign up to set email alerts
|

Diterpene Resin Acids and Olefins in Calabrian Pine (Pinus nigra subsp. laricio (Poiret) Maire) Oleoresin: GC-MS Profiling of Major Diterpenoids in Different Plant Organs, Molecular Identification and Expression Analysis of Diterpene Synthase Genes

Abstract: A quali-quantitative analysis of diterpenoid composition in tissues obtained from different organs of Pinus nigra subsp. laricio (Poiret) Maire (Calabrian pine) was carried out. Diterpene resin acids were the most abundant diterpenoids across all the examined tissues. The same nine diterpene resin acids were always found, with the abietane type prevailing on the pimarane type, although their quantitative distribution was found to be remarkably tissue-specific. The scrutiny of the available literature revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Taken together, the above results suggested that the quantitatively profile of monoterpenes in P. laricio is remarkably tissue-specific, and the perusal of the available literature indicated a species specificity as well; thus, confirming our previous results on the diterpenoids from the same conifer species [ 28 ]. As it was shown by several studies [ 10 , 30 , 31 ], there is a notable variation in the monoterpene composition between different genera and species of conifer trees.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Taken together, the above results suggested that the quantitatively profile of monoterpenes in P. laricio is remarkably tissue-specific, and the perusal of the available literature indicated a species specificity as well; thus, confirming our previous results on the diterpenoids from the same conifer species [ 28 ]. As it was shown by several studies [ 10 , 30 , 31 ], there is a notable variation in the monoterpene composition between different genera and species of conifer trees.…”
Section: Resultssupporting
confidence: 89%
“…Another aspect of potential interest in the non-model conifer species studied here, in view of its possible physiological, ecological, and technological implications, concerns the reciprocal quantitative relationships among the major terpenoids components of oleoresin, as well as the developmental and environmental factors driving the differential distribution of them in plant tissues. In our aforementioned twin study [ 28 ], we analysed quantitatively, in the identical plant material studied here and by adopting an essentially similar GC–MS approach, the diterpenoid components of oleoresin in the form of diterpene resin acids (DRAs), i.e., the stable and functional conformers deriving from the combined action of DTPSs and of cytochrome P450 monooxygenases [ 1 ]. By comparing the results obtained in the two experiments ( Figure 1 and [ 28 ]) on a DW basis, total monoterpenes as a whole in P. laricio are about six times more abundant than total DRAs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations